Aplikasi Penginderaan Jauh dan SIG Pemetaan Pengunaan Lahan dan Sistem Informasi Lahan Pertanian (Studi Kasus di Kabupaten Nagekeo, Provinsi Nusa Tenggara Timur) - Paul Ludgerius Rusman Pita; Indayati Lanya; I Ketut Sardiana (Agriculture Faculty of Flores University, 2023)
Remote sensing technology combined with Geographic Information Systems (GIS) can provide and produce data and information quickly, precisely, and accurately, so that the latest land use can be known. This study aims to determine the level of accuracy of satellite imagery interpretation, make existing land use maps, and provide agricultural land information systems in Nagekeo Regency. The research method used is an explorative method. The stages of the research consisted of identifying satellite images, field surveys, reinterpreting land use maps, and creating agricultural land information systems. The results showed that the level of accuracy of interpretation of satellite imagery for land use in Nagekeo Regency was 97%. The widest use of paddy fields is in Aesesa Subdistrict with 5080 ha, the widest use of dry land is in Nangaroro Subdistrict with 2062 ha, the widest use of mixed garden land is in Boawae Subdistrict with 7062 ha and the widest use of garden land is in Mauponggo Subdistrict 2800 ha. Information on paddy fields contains information on land area, land status, farmer's name, farmer's address, farmer's age, cropping pattern, and yield sharing system. The total land ownership of the owner's land was 2417.77 ha with a total of 2798 plot units, 1102.7 ha of sharecroppers' land with a total of 1240 plot units, and pawning farmer's land area of 233.99 ha with a total of 331 plot units.